Educational differences in mental health-related quality of life during the COVID-19 pandemic in Germany: the mediating role of pandemic-induced psychosocial stress - Kersjes, Christina; Demirer, Ibrahim; Pförtner, Timo-Kolja; Beese, Florian; Hoebel, Jens; Schnitzer, Susanne; Mauz, Elvira (Frontiers in Public Health, 2025)
ObjectivesA large body of evidence shows poorer mental health among lower socioeconomic groups, with chronic stress being an important pathway in this relationship. It was expected that the mental health of people with low socioeconomic status may have been particularly affected by the COVID-19 pandemic. While it has been established that stress also impacted mental health during the pandemic, the aim of this study was to analyze if pandemic-induced psychosocial stress (PIPS) mediated educational differences in mental health-related quality of life (MHRQOL) and which life domains were particularly affected.MethodsThe data came from the population-based representative study “Corona Monitoring Nationwide – Wave 2 (RKI-SOEP-2),” from November 2021–February 2022, restricted to the working age population (18–67 years, n = 7,425). The mediating role of PIPS in educational differences (fractional rank variable from 0 [lowest] to 1 [highest education]) in MHRQOL was assessed for the life domains family, partnership, financial situation, work/school, social life, and leisure time. We used causal mediation analysis to estimate the total, indirect, and direct effects.ResultsMHRQOL increased with higher education. Higher education was associated with more PIPS in the domain’s family, social life, and leisure time, while lower education was associated with more financial PIPS. PIPS in the life domains family, financial situation, leisure time, and social life significantly mediated educational differences in MHRQOL. No significant mediation effect was found for partnership and work/school PIPS.ConclusionPIPS contributed to educational differences in MHRQOL, with different educational levels showing more stress in different life domains. Group-targeted and life domain-specific approaches for prevention and intervention should be considered.